"Maybe not 100%": Co-constructing language proficiency in the Maya diaspora. Issue 4 (2nd October 2022) - Canizales, Stephanie L.; O'Connor, Brendan H.
ABSTRACT: Language learning and the development of language proficiency are central concerns in the study of immigrant adaptation. This paper analyzes the social construction of language proficiency among Indigenous Guatemalan Maya youth in the United States– specifically, undocumented young adults who migrated to Los Angeles, California as unaccompanied minors and who grew up as low-wage workers. Our analysis shows that youth used "percentage talk"– i.e., construing current proficiency as apercentage of idealized full proficiency– as a discursive strategy to assess their language ability and level of social adaptación (adaptation) relative to native English and Spanish speakers, other Indigenous language speakers, and their past selves. Through percentage talk, youth wrestled with social stratification and inequality in the U.S. and Guatemala and imagined themselves as future members of Spanish- and English-oriented discourse communities. While outwardly individualistic, percentage talk also allowed youth to gauge their ability to support the language socialization and social incorporation of other L1 Maya speakers in diaspora. Youth's tricultural adaptation and contestation of an all-or-nothing ideology of proficiency shows their nuanced understanding of the role of language in immigrant socialization.